Correlation between Interleukin-17, High Sensitivity C-Reactive Protein and Pepsinogen in Helicobacter pylori Infected Gastritis - Jeanne Winarta; Bradley Jimmy Waleleng; Nelly Tandean Wenas; Fujiyanto; Oscar Miguna; Marco Rahardja (Gastroenterology Insights, 2024)
Gastritis is an inflammatory process in the gastric mucosa and submucosa caused by Helicobacter pylori (H. pylori). The infection modulates immune components, such as interleukin (IL) 17, high sensitivity C-reactive protein (hsCRP) and pepsinogen. This study aimed to determine the relationship between IL-17, hsCRP and pepsinogen in H. pylori infected gastritis. This observational cross-sectional study was conducted at Prof. Dr. R. D. Kandou General Hospital Manado from May-July 2022. Measurement of blood sample levels of IL-17, hsCRP, pepsinogen I, pepsinogen II and pepsinogen I/II ratio. Spearman’s statistical test was used to determine correlations between these variables. This study involved 48 patients aged 21–64, with a majority of females (67%). IL-7 had a positive correlation with pepsinogen I (r = 0.292; p = 0.044) and pepsinogen II (r = 0.288; p = 0.047) in H. pylori infected gastritis. Meanwhile, IL-17 with pepsinogen I/II ratio, hsCRP with pepsinogen I, pepsinogen II, pepsinogen I/II ratio and IL-17 with hsCRP did not show a significant correlation (p > 0.05). There was a correlation between IL 17 to pepsinogen I and pepsinogen II in gastritis infected with H. pylori, suggesting the importance of these early markers of inflammation in determining the severity of gastric mucosal inflammation in pylori-infected patients.